Evaluasi Status Kesuburan Tanah Sawah Berbasis Sistem Informasi Geografis di Kecamatan Negara Kabupaten Jembrana - PEDRO BARUS; I DEWA MADE ARTHAGAMA; I MADE MEGA (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2022)
Evaluation of Rice Field Fertility Status Based on Geographical Information System in Negara District, Jembrana Regency Lowland rice production at Negara District in 2014 was 6.89 tons/ha and in 2015 decreased to 6.67 tons/ha. This is thought to be due to the reduced ability of the land to support the agricultural production process. The purpose of this study was to determine the status of soil fertility and the parameters of the limiting factors of soil fertility, to make a map of the status of soil fertility, and to provide direction for the management of soil fertility. This research was conducted from December 2021 – March 2022. The methods used in this study included survey and soil test methods with parameters of fertility status including CEC; BS; organic C; total P and total K. The results showed two soil fertility statuses in the study area, namely low in HLU I (Pengembengan Village, West Tegal Badeng, East Badeng Tegal, Baluk, Banyubiru, Kaliakah, Lelateng, Bale Agung Baler) and HLU II (Pengambengan Village, East Tegal Badeng, Banyubiru, Lelateng) and moderate soil fertility in HLU III (Kaliakah Village, Berangbang, Bale Agung Baler) and HLU IV (Kaliakah Village, Berangbang, Bale Agung Village). The limiting factors for soil fertility status were CEC and moderate K2O content and low organic C content. The direction of soil fertility management is the addition of organic matter and K fertilizer to improve soil fertility status.